2019
DOI: 10.1017/s002966511800277x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and improving adherence to the gluten-free diet in people with coeliac disease

Abstract: Coeliac disease (CD) is an autoimmune gastrointestinal disorder whereby the ingestion of gluten, a storage protein found in wheat, barley and rye, causes damage to intestinal mucosa with resultant malabsorption, increased risk of anaemia and osteoporosis. Worldwide estimates suggest 1% of the population have CD. With no cure, the only treatment is a gluten-free diet (GFD). Adhering to a GFD can be very challenging; it requires knowledge, motivation and modified behaviours. Assessing adherence to a GFD is metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 97 publications
5
67
1
4
Order By: Relevance
“…Furthermore, the difference observed did not resist after the Bonferroni correction. However, depressive disturbances can substantially affect the quality of life and are a reliable marker of poor adherence to the diet [ 68 ]. Screening CD subjects for depressive symptoms is therefore crucial, including follow-up visits, to promptly suggest appropriate pharmacotherapy and/or psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the difference observed did not resist after the Bonferroni correction. However, depressive disturbances can substantially affect the quality of life and are a reliable marker of poor adherence to the diet [ 68 ]. Screening CD subjects for depressive symptoms is therefore crucial, including follow-up visits, to promptly suggest appropriate pharmacotherapy and/or psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional cereal-based gluten-containing foodstuffs such as bread, pasta, and beer must be replaced by corresponding surrogates made from raw materials that do not contain gluten. However, a lifelong strict GFD is not easy, due to gluten ubiquity, cross-contamination of foods, improper labeling, and social constraints [ 20 , 26 ] and, therefore, a considerable portion of patients with CD do not adhere to a GFD. Numerous studies have investigated the factors influencing the compliance to a GFD, showing that adherence rates in patients with CD are well below optimal.…”
Section: Adherence To a Gfdmentioning
confidence: 99%
“…For example, 38 studies, published up to 2007, indicated an adherence rate ranging between 42 and 91% [ 89 ]. More recently, compliance with a GFD has been reported to be in the range of approximately 45 to 90% [ 20 ]. In the case of children, a systematic review of 49 studies, published up to 2018, revealed adherence rates ranging from 23 to 98% ( Table 1 ) [ 90 ].…”
Section: Adherence To a Gfdmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse contexto, salienta-se a ampliação pela busca por alimentos isentos de glúten, no entanto, a disponibilidade, o dispêndio e a obtenção limitada desses alimentos são fatores capazes intervir no seguimento do tratamento dietético. Desse modo, pontua-se o impacto que certos aspectos refletem na qualidade de vida dos celíacos, dentre eles, pode-se citar: os valores onerosos, a monotonia alimentar e o valor nutricional inferior dos produtos alimentares exclusos de glúten em comparação aos que contém glúten (Hopman, 2008;Muhammad, Reeves & Jeanes, 2019). Research, Society andDevelopment, v. 9, n. 10, e3529108794, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8794 4 Nos últimos anos, nota-se uma crescente pesquisa para a substituição da farinha de trigo por outras matérias-primas alternativas sem glúten, visando desenvolvimento de novos produtos.…”
Section: Introductionunclassified